Інституційне забезпечення конкуренції на регіональних ринках житлової нерухомості - Павлов, Костянтин Володимирович; Pavlov, Kostiantyn V. (Мукачевський державний університет, 2017)
В даній статті визначено та досліджено рівень інституційного забезпечення конкурентних відносин на ринку житлової нерухомості. За критеріями розподілу окреслено суб'єктну структуру ринку житлової нерухомості. Проаналізовано окремі чинники, що впливають на інституційне забезпечення ринку житлової нерухомості, а також запропоновано шляхи їх забезпечення та регулювання з боку держави.

This article defnes and examines the level of institutional provision of competitive relations in the residential real estate market. According to the distribution criteria, the subjective structure of the residential real estate market is indicated. Some factors infuencing the institutional provision of the residential real estate market are analyzed, as well as ways of ensuring and regulating them on the part of the state are proposed.
Institutional protection of competition in regional markets of residential properties
Keywords: інституції; державне інституційне забезпечення; інституційна інфраструктура; конкуренція; конкурентні відносини; ринок житлової нерухомості; девелопери; інвестори; ріелтори; institutes; state institutional support; institutional infrastructure; competition; competitive relations; residential real estate market; developers; investors; realtors